The effectiveness of mobile-based teaching materials for academic writing in hybrid learning on students’ academic writing ability - Cahyo Hasanudin; Aida Azizah; Ayu Fitrianingsih; Nofia Fitriyana; Abather Saadoon (Universitas Ahmad Dahlan, 2024)
Mobile-based teaching materials for academic writing are flexible to be implemented in various learning models. Therefore, this study aims to investigate which is more effective between mobile-based teaching materials in hybrid learning and teaching materials in form of handouts in direct instruction to produce students’ academic writing ability. This study is quasi experimental design in which the population is all of students in second semester at Indonesian language and literature department of IKIP PGRI Bojonegoro. They are consisted of 72 students. Research samples are taken using simple random sampling. Test is utilized to obtain the data. Moreover, its hypothesis is tested using t-test. Result of study shows that in the significance level of 0,05, it equals 1,6992. While the value of t0,05;70 = 1,6669. Based on t table, the value of DK = . tobs DK. In other words, H0 is rejected. It can be concluded that mobile-based teaching material of academic writing skill in hybrid learning is more effective to produce students’ academic writing ability than the teaching materials in form of handouts in direct instruction.